Metabolic Imaging to Assess Treatment Response to Cytotoxic and Cytostatic Agents - Serkova, Natalie J.; Eckhardt, S. Gail (Frontiers in Oncology, 2016)
For several decades, cytotoxic chemotherapeutic agents were considered the basis of anti-cancer treatment for patients with metastatic tumors. A decrease in tumor burden, assessed by volumetric computed tomography (CT) and magnetic resonance imaging (MRI), according to the Response Evaluation Criteria in Solid Tumors (RECIST), was considered as a radiological response to cytotoxic chemotherapies. In addition to RECIST-based dimensional measurements, a metabolic response to cytotoxic drugs can be assessed by positron emission tomography (PET) using 18F-fluoro-thymidine (FLT) as a radioactive tracer for drug-disrupted DNA synthesis. The decreased 18FLT-PET uptake is often seen concurrently with increased apparent diffusion coefficients (ADC) by diffusion weighted imaging (DWI) due to chemotherapy-induced changes in tumor cellularity. Recently, the discovery of molecular origins of tumorogenesis led to the introduction of novel signal transduction inhibitors (STIs). STIs are targeted cytostatic agents; their effect is based on a specific biological inhibition with no immediate cell death. As such, tumor size is not anymore a sensitive end-point for a treatment response to STIs; novel physiological imaging end-points are desirable. For receptor tyrosine kinase inhibitors as well as modulators of the downstream signaling pathways, an almost immediate inhibition in glycolytic activity (the Warburg effect) and phospholipid turnover (the Kennedy pathway) has been seen by metabolic imaging in the first 24 hours of treatment. The quantitative imaging end-points by magnetic resonance spectroscopy (MRS) and metabolic PET (including 18F-fluoro-deoxy-glucose, FDG, and total choline) provide an early treatment response to targeted STIs, before a reduction in tumor burden can be seen.